4-Methylesculetin, a natural coumarin with intestinal anti-inflammatory activity, elicits a glutathione antioxidant response by different mechanisms - Tanimoto, Alexandre [UNESP] (2020)
4-methylesculetin (4 ME) is a natural antioxidant coumarin with protective effects on the intestinal inflammation, in which oxidative stress plays a key role in its aetiology and pathophysiology. Based on this, we examined the antioxidant molecular mechanisms involved in the intestinal anti-inflammatory activity of the 4 ME. For this purpose, we investigated the effects of the 4 ME on the modulation of gene expression and antioxidant-related enzyme activities in TNBS model of intestinal inflammation as well as the molecular interaction between 4 ME and glutathione reductase. Our results showed that 4 ME modulated glutathione-related enzymes, mainly increasing glutathione reductase activity. These effects were related to upregulation of glutathione reductase and Nrf2 gene expression. Fluorescence and nuclear magnetic resonance data showed that interaction between 4 ME and glutathione reductase is collisional, hydrophobic and spontaneous, in which C4 methyl group is the second epitope most buried into glutathione reductase. Molecular modelling calculation showed Lys70-B, Arg81-A, Glu381-B, Asp443-A, Ser444-A, Glu447-B and Ser475-A participated in electrostatic interaction, Lys70-B, Glu381-B and Arg81-A acted in the hydrophobic interactions and Trp73, Phe377 and Ala446 are responsible for the hydrogen bonds. Based on this, our results showed 4 ME acted by different mechanisms to control oxidative stress induced by intestinal damage, controlling the imbalance between myeloperoxidase activity and glutathione production, upregulating the glutathione S-transferase and glutathione reductase activities, preventing the Nrf2 and glutathione gene expression downregulation with consequent glutathione maintenance. Finally, 4 ME interacted at molecular level with glutathione reductase, stabilizing its enzymatic activity and reducing oxidative stress to take place in intestinal inflammatory process.